Magpalaya para sa halata a digital awareness campaign celebrating effeminacy among queer men engaged in casual sexual relationships and experiences - Reyes, John Vincent; Dans, Sandra Michelle (Quezon City College of Fine Arts, University of the Philippines Diliman, 2024)
Casual sexual relationships and experiences (CSREs) provide queer men the space to experience intimacy and community building, allowing for personal exploration of gender and sexual identity. However, as evident in geo-social networking applications (GSNAs) like Grindr, CSREs among queer men are tainted by internalized discrimination.

In the Philippines, the term pass sa halata has reportedly been used to discriminate against effeminate queer men engaged in the casual sexual space. Influenced by heterosexism--the idea that being straight (cisgender and cis-heteornormative) is the most valid expression of gender and sexuality--queer men are conditioned to discriminate against their own sexual identity of against expressions of effeminacy, resulting in internalized homophobia and femmephobia, respectively.

Examining the social context of CSREs and internalized discrimination, this study delves into the experience of queer men engaged in CSREs via Grindr, aged 18-28, within the Greater Manila area. Through the needs-finding process, it was identified that queer men are compelled by heterosexism to disproportionately favor masculinity. This results in instances of self-devaluation and microaggression through fabrication of masculinity, concealment of effeminacy, and discrimination against effeminate queer men.

This study proposes a solution to the design problem: how might we uplift the status of femininity among queer men engaged in CSREs aged 18 - 28? through a digital awareness campaign celebrating effeminacy among queer men. The study intervention proved that an authentic, immersive, and humanizing approach to community education proved effective in reducing internalized influences of heterosexism. Demonstrated as empathy through self-exploration, the proposed intervention suggested that by liberating ourselves from influences of internalized discrimination, we also empower those marginalized and discriminated.
Thesis (Bachelor of Fine Arts in Visual Communication) -- University of the Philippines Diliman
Bibliography: leaves 113-123
Keywords: Sexual minority culture; Heterosexism; Effeminacy